Comparative Genomics Reveals Thousands of Novel Chemosensory Genes and Massive Changes in Chemoreceptor Repertories across Chelicerates. (18th April 2018) - Vizueta, Joel; Rozas, Julio; Sánchez-Gracia, Alejandro
Abstract: Chemoreception is a widespread biological function that is essential for the survival, reproduction, and social communication of animals. Though the molecular mechanisms underlying chemoreception are relatively well known in insects, they are poorly studied in the other major arthropod lineages. Current availability of a number of chelicerate genomes constitutes a great opportunity to better characterize gene families involved in this important function in a lineage that emerged and colonized land independently of insects. At the same time, that offers new opportunities and challenges for the study of this interesting animal branch in many translational research areas. Here, we have performed a comprehensive comparative genomics study that explicitly considers the high fragmentation of available draft genomes and that for the first time included complete genome data that cover most of the chelicerate diversity. Our exhaustive searches exposed thousands of previously uncharacterized chemosensory sequences, most of them encoding members of the gustatory and ionotropic receptor families. The phylogenetic and gene turnover analyses of these sequences indicated that the whole-genome duplication events proposed for this subphylum would not explain the differences in the number of chemoreceptors observed across species. A constant and prolonged gene birth and death process, altered by episodic bursts of gene duplication yielding lineage-specific expansions, has contributed significantly to the extant chemosensory diversity in this group of animals. This study also provides valuable insights into the origin and functional diversification of other relevant chemosensory gene families different from receptors, such as odorant-binding proteins and other related molecules.